Dominant particles and reactions in a two-temperature chemical kinetic model of a decaying SF6 arc. (8th February 2016) - Wang, Xiaohua; Gao, Qingqing; Fu, Yuwei; Yang, Aijun; Rong, Mingzhe; Wu, Yi; Niu, Chunping; Murphy, Anthony B
Abstract: This paper is devoted to the computation of the non-equilibrium composition of an SF6 plasma, and determination of the dominant particles and reactions, at conditions relevant to high-voltage circuit breakers after current zero (temperatures from 12 000 K to 1000 K and a pressure of 4 atm). The non-equilibrium composition is characterized by departures from both thermal and chemical equilibrium. In thermal non-equilibrium process, the electron temperature ( T e ) is not equal to the heavy-particle temperature ( T h ), while for chemical non-equilibrium, a chemical kinetic model is adopted. In order to evaluate the reasonableness and reliability of the non-equilibrium composition, calculation methods for equilibrium composition based on Gibbs free energy minimization and kinetic composition in a one-temperature kinetic model are first considered. Based on the one-temperature kinetic model, a two-temperature kinetic model with the ratio T e / T h varying as a function of the logarithm of electron density ratio ( n e / ) was established. In this model, T * is introduced to allow a smooth transition between T h and T e and to determine the temperatures for the rate constants. The initial composition in the kinetic models is obtained from the asymptotic composition as infinite time is approached at 12 000 K. The molar fractions of neutral particles and ions in the two-temperature kinetic model are consistent with the equilibrium composition and the composition obtained from the one-temperature kinetic model above 10 000 K, while significant differences appear below 10 000 K. Based on the dependence of the particle distributions on temperature in the two-temperature kinetic model, three temperature ranges, and the dominant particles and reactions in the respective ranges, are determined. The full model is then simplified into three models and the accuracy of the simplified models is assessed. The simplified models reduce the number of species and reactions by a factor of about 2, while providing results that agree closely with the full model. Thus, the physicochemical processes of SF6 arc can be characterized by relatively few species and reactions in each temperature range. It is noted that the simplified models can also be applied to a wide range of pressures, 1–16 atm, conditions which cover most circuit breaker applications. The simplified species and reactions will allow the computing time of multi-dimensional models, taking into account departures from both thermal and chemical equilibrium, to be decreased dramatically while capturing the main physicochemical processes in SF6 arcs.